Pemaknaan Islam Moderat Sebagai Sebuah Terminologi - Dedi Sahputra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This article aims to find out the meaning of the term moderate Islam as a terminology. The problem is focused on reviewing the language and its history, as well as from the context of the political interests that lie behind it. In order to approach the problem, this article uses a reference to the theory of terminology. The data were collected through a literature review of various similar studies that have been conducted. Furthermore, the data obtained were analyzed qualitatively. This study concludes that there is a bias in understanding the terminology of moderate Islam which lies in equating the word "Islam" with the word "ummah", so that the term "ummatan wasatan" is then equated with "moderate Islam". This interpretation bias is strongly influenced by the global political context related to the emergence of the term terrorism and the concept of the global war on terrorism (GWOT) which was coined by the United States during the George W. Bush Junior administration.